Shoot and Root Growth in Common Bean (Phaseolus vulgaris L.) Exposed to Gradual Drought Stress - Laily Ilman Widuri; Benyamin Lakitan; Erizal Sodikin; Mery Hasmeda; Mei Meihana; Kartika Kartika; Erna Siaga (AGRIVITA, Journal of Agricultural Science, 2018)
Drought condition during the dry season is a major constraint for intensifying agricultural activities at riparian wetlands in Indonesia, particularly for annual vegetables, including common bean (Phaseolus vulgaris L.). Besides inhibiting growth and reducing yield, drought also causes alteration of the shoot and root growth and development. The objective of this study was to evaluate responses of common bean to three durations of drought stress and the bean ability to recover after termination of the stress treatments. Gradual drought stress treatments were imposed by withholding all water sources to the treated plants. Three durations of drought stress imposed were 4, 8, and 12 days. The ability of the stress-treated plants to recover was evaluated at 7 days after termination of each treatment. The result of this study revealed that common bean was able to tolerate and recover from gradual water deficit for up to 8 days; however, prolonged water deficit for 12 days inhibited the growth of above-ground organs in common bean. Despite root regrowth during the recovery period, plants previously treated with 12 days of drought were unable to recover but those treated with shorter drought stress period were able to recover.